Brazil's steel city : developmentalism, strategic power, and industrial relations in Volta Redonda, 1941-1964 - Dinius, Oliver J. (Oliver Jürgen) (Stanford University Press, 2011)
This text presents a social history of the National Steel Company (CSN), Brazil's foremost state-owned company and largest industrial enterprise in the mid-20th century.